International Society : Diverse Ethical Perspectives - Nardin, Terry, 1942-; Mapel, David, 1952- (Book collections on Project MUSE., 1999)
Drawing on diverse philosophical and theological perspectives, the contributors to this collection debate the character of international society, the authority of international law and institutions, and the demands of international justice.